Abdominal and gluteofemoral fat depots show opposing associations with postprandial lipemia. Issue 4 (13th July 2021) - Christiansen, Malene R; Ureña, Mario G; Borisevich, Dmitrii; Grarup, Niels; Martínez, J Alfredo; Oppert, Jean-Michel; Sørensen, Thorkild Ia; Hansen, Torben; Blaak, Ellen E; Kilpeläinen, Tuomas O
ABSTRACT: Background: High postprandial lipemia is associated with increased risk of cardiovascular disease, independently of fasting lipid concentrations. Abdominal and gluteofemoral fat depots handle lipoproteins differently, which could affect postprandial lipemia and contribute to the relation between abdominal fat distribution and cardiovascular disease risk. Objectives: We aimed to study the influences of higher abdominal compared with gluteofemoral fat on postprandial lipemia after a high-fat meal in individuals with obesity. Methods: A total of 755 adults with obesity from a randomized controlled trial in 7 European countries consumed a liquid high-fat meal. Concentrations of triglycerides (TG), glycerol, free fatty acids, and the cholesterol component of remnant-like particles (RLP), LDL, and HDL were measured postprandially for 3 h. Associations of waist circumference (WC), hip circumference (HC), and waist-hip ratio (WHR) with changes in postprandial lipid concentrations, adjusted for fasting concentrations and BMI, were examined using linear regression models. To assess whether the association of WHR with postprandial lipemia could be causal, we performed instrumental variable analyses using a genetic score of 442 variants known to be associated with WHR adjusted for BMI in 2-stage least-squares regression models. Results: WHR was associated with higher TG and RLP cholesterol concentrations, independent of fasting lipid concentrations and BMI. Instrumental variable analyses suggested that the associations of WHR with postprandial TG (β = 0.038 μmol/L*min, SE = 0.019 μmol/L*min, P = 0.044) and RLP cholesterol concentrations (β = 0.059 mmol/L, SE = 0.025 mmol/L, P = 0.020) may be causal. WC and HC showed opposite effects: higher WC was associated with higher TG and RLP cholesterol concentrations whereas higher HC was associated with lower concentrations. Conclusions: Our results suggest that higher fat deposition abdominally versus gluteofemorally may be causally associated with elevated postprandial lipemia after a high-fat meal, independent of fasting lipid concentrations and BMI. Furthermore, higher abdominal and gluteofemoral fat depots show opposing effects on postprandial lipemia. This trial was registered at www.isrctn.com as ISRCTN25867281.